The Irish short story at the turn of the twenty-first century - Armie, Madalina, 1991- author.
1 online resource (ix, 242 pages).
Keywords: "In the mid-1990s, Ireland was experiencing the 'best of times'. The Celtic Tiger seemed to instil in the national consciousness that poverty was a problem of the past. The impressive economic performance ensured that the Republic occupied one of the top positions among the world's economic powers. During the boom, dissident voices continuously criticised what they considered to be a mirage, identifying the precariousness of its structures and foretelling its eventual crash. The 2008 recession proved them right. Throughout this time, the Irish contemporary short story expressed distrust. Enabled by its capacity to reflect change with immediacy and dexterity, the short story saw through the smokescreen created by the Celtic Tiger discourse of well-being. It reinterpreted and captured the worst and the best of the country and became a bridge connecting tradition and modernity. The major objective of this book is to analyse the interactions between fiction and reality during this period in Ireland by studying short stories written by old and emergent voices published between the birth of the Celtic Tiger in 1995 up to its immediate aftermath in 2013"--